Influence of stoichiometry and structure on the optical properties of AlNxOy films - Borges, Joel Nuno Pinto (2013)
The AlNxOy system offers the possibility to obtain a wide range of responses, by tailoring the properties between Al, AlN and Al2O3, opening a significant number of possible applications. The aim of this work is to correlate the optical properties of AlNxOy thin films with their composition and structural features, taking as reference the binary systems AlNx and AlOy. In the AlNx system, the increase of the nitrogen content induced a wide variation in the optical properties, ranging from the typical profile of a polycrystalline Al-type film towards nearly constant reflectance values as low as 5%, as well as a smooth increase in samples transparency as the ratio N/Al approached unit. In the case of the AlOy system, the reflectance also decreased as the oxygen content increased, however the transition to transparent films (Al2O3-like) was more abrupt. The ternary system AlNxOy, revealed optical responses that ranged from a typical profile of a polycrystalline Al-type film, towards low and constant reflectance values in a wide range of x and y coefficients, ending up as semi-transparent when Al2O3-like films were formed. The unusual low optical reflectance of some films reveals some potential applications in solar power systems and sensors.